2021
DOI: 10.48550/arxiv.2112.00267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CAMA: Energy and Memory Efficient Automata Processing in Content-Addressable Memories

Abstract: Accelerating finite automata processing is critical for advancing real-time analytic in pattern matching, data mining, bioinformatics, intrusion detection, and machine learning. Recent in-memory automata accelerators leveraging SRAMs and DRAMs have shown exciting improvements over conventional digital designs. However, the bit-vector representation of state transitions used by all state-of-the-art (SOTA) designs is only optimal in processing worst-case completely random patterns, while a significant amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Our experiments show that using counters and bit vectors outperforms unfolding solutions by orders of magnitude. Moreover, in experiments with realistic workloads, we have observed that our design can provide up to 76% energy reduction and 58% area reduction in comparison to CAMA [26], a state-of-the-art in-memory NFA processor.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Our experiments show that using counters and bit vectors outperforms unfolding solutions by orders of magnitude. Moreover, in experiments with realistic workloads, we have observed that our design can provide up to 76% energy reduction and 58% area reduction in comparison to CAMA [26], a state-of-the-art in-memory NFA processor.…”
Section: Discussionmentioning
confidence: 86%
“…In this section, we present our hardware design for efficiently executing NCAs. We augment a state-of-the-art inmemory NFA acceleration architecture called CAMA [26] with counter and bit vector modules. We report hardware simulation results in both microbenchmarks and application benchmarks.…”
Section: Hardware Implementation and Experimentsmentioning
confidence: 99%
See 2 more Smart Citations